Parallel Class Ranking Model Using Analytic Hierarchy Process With Multi Criteria - Kusuma, Dedy Hidayat; Nur Shodiq, Moh; Kurnia Fitriani, Indah (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
Madrasah Aliyah Negeri (MAN) Banyuwangi using a worksheet which can lead to error occurrences and slow decision making. A system for decision support that can improve the ranking process and quality were developed in this paper. The proposed system implemented the codeigniter framework, MySQL database, and PHP programming language. The system provided three user roles which are teacher, student, and administrator role. These four parameters are used as ranking system input, including academic values, non-academic values, violation scores, and student attendance. The ranking process was conducted by applying the analytic hierarchy process (AHP) method. The developed decision support system was tested using two ways: the black box testing method and providing questionnaires. Black box testing result shows that the system has functionally worked, while user’s questionnaire gives 92,29% well accepted by users. The results show that the decision support system can help manage values and determine the parallel ranking list.